Methodological and organizational framework for managerial control at company level - M.Y. Gedz (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
Increased competition and diversification, business transnationalization, involvement of largest corporate entities in all kinds of social management require new approaches to building adequate control systems that can ensure competitiveness at company level. The aim of the paper is to improve methodological framework for managerial control organization system at company level.Managerial control can be presented as a system consisting of the following elements: managerial information system, responsibility centers, control techniques, control procedures, controlled environment, accounting system, controlling personnel. The above control elements are analyzed. The main objectives of internal control system, main indicators of management performance and efficiency of control, elements and implementation phases of internal control system are defined.To assess the efficiency of internal control system, use the three levels of control risk is suggested: high, moderate, low. A flowchart for assessment of the level of control risk is constructed.It is concluded that internal control at company level is an important factor of management efficiency and an important issue of corporate management. One of the major management tasks is to develop, introduce and improve standardized control systems programs for companies, especially public ones listed at stock exchange. These programs need to consider organizational and legal forms, size and management structure of companies.